RACISM: AFRICAN AMERICANS’ EXPERIENCES AS VICTIMS OF SLAVERY AND SEGREGATION AS IMPLEMENTED BY THE POLICIES OF WHITE SUPREMACY - Bedell, Fred (International Journal of Research -GRANTHAALAYAH, 2021)
This essay will be divided into three parts – Slavery, Segregation, and Past and Recent Events that will document the impact on the social, political, and economic fabric of marginalized communities. It will focus on the social construct theory of domination and subordination and the caste system that subjugated African Americans under the guise of white supremacy